R. G. Collingwood a research companion - Connelly, James 1957-; Johnson, Peter; Leach, Stephen (Bloomsbury Academic, 2015)
"R G Collingwood is an important twentieth century historian, archaeologist and philosopher whose works are the subject of continued interest, analysis and study. There is an unquestionable need to support this research activity with the provision of a reference guide which is fully up-to-date, informed and authoritative. The Companion will therefore list all primary and secondary material relevant to the study of Collingwood in all his fields of expertise - historical theory, philosophy and archaeology. It will also provide a guide to archive material relevant to his life, together with sources and locations. The resulting volume will provide an essential companion to the understanding of the life and thought of R G Collingwood"..
Keywords: Collingwood, R. G. -- (Robin George), -- 1889-1943; Collingwood, Robin G. -- 1889-1943; PHILOSOPHY / History & Surveys / Modern; POLITICAL SCIENCE / History & Theory; HISTORY / Modern / 20th Century; Bibliografie; Aufsatzsammlung